DELINEASI NILAI RESISTIVITAS DI LAPANGAN PANAS BUMI TAMBANG SAWAH MENGGUNAKAN METODE MAGNETOTELLURIK - Andre Rahmat Al Ansory; Hana Raihana; Vinki Loverly Pritama; Welly Saputri; Faritz Bagda Maghribi; Muchammad Farid; Arif Ismul Hadi; Halauddin; Budi Harlianto; Nanang Sugianto (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2023)
The subsurface structure of the geothermal field in Desa Tambang Sawah has been mapped. This research aims to delineate the resistivity values in the area of Tambang Sawah Village, Lebong Regency, Bengkulu Province based on magnetotelluric measurements which can later identify low, medium, and high resistivity values to interpret geothermal in the research area. The magnetotelluric (MT) method with electrical and magnetic sensors is used to collect data in the field. There are two electrical sensors in horizontal direction (Ex, Ey) and three magnetic sensors in horizontal direction. (Hx, Hy) and vertical (Hz). The results obtained from this study are that resistivity values of 20-50 ohm.m are considered as reservoirs, while resistivity of 0.26-0.8 ohm.m is considered as caprock, and resistivity greater than 300 ohm.m is considered as hot rock.